2021
DOI: 10.1021/acs.joc.1c01491
|View full text |Cite
|
Sign up to set email alerts
|

SNAr Radiofluorination with In Situ Generated [18F]Tetramethylammonium Fluoride

Abstract: This report describes a method for the nucleophilic radiofluorination of (hetero)­aryl chlorides, (hetero)­aryl triflates, and nitroarenes using a combination of [18F]­KF·K2.2.2 and Me4NHCO3 for the in situ formation of a strongly nucleophilic fluorinating reagent (proposed to be [18F]­Me4NF). This method is applied to 24 substrates bearing diverse functional groups, and it generates [18F]­(hetero)­aryl fluoride products in good to excellent radiochemical yields in the presence of ambient air/moisture. The rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Finally, during the completion of this review, the Sanford group reported the first in situ generation of [ 18 F]-TMAF for the nucleophilic radiofluorination of heteroaromatic molecules [99]. This method delivered a relatively wide range of [ 18 F]-(hetero)aryl fluoride products with good to excellent yields in the presence of ambient air and moisture, and involves the swift metathesis of an easy-to-dry quaternary methylammonium salt, such as Me 4 NHCO 3 , with the well-known source of [ 18 F]fluoride, [ 18 F]KF•K 2.2.2 , which in practice is much less hygroscopic than the [ 18 F]R 4 NF salts traditionally used for this purpose.…”
Section: Preparation Of Tmafmentioning
confidence: 99%
“…Finally, during the completion of this review, the Sanford group reported the first in situ generation of [ 18 F]-TMAF for the nucleophilic radiofluorination of heteroaromatic molecules [99]. This method delivered a relatively wide range of [ 18 F]-(hetero)aryl fluoride products with good to excellent yields in the presence of ambient air and moisture, and involves the swift metathesis of an easy-to-dry quaternary methylammonium salt, such as Me 4 NHCO 3 , with the well-known source of [ 18 F]fluoride, [ 18 F]KF•K 2.2.2 , which in practice is much less hygroscopic than the [ 18 F]R 4 NF salts traditionally used for this purpose.…”
Section: Preparation Of Tmafmentioning
confidence: 99%
“…Conversely, a wider range of stable N-difluoromethyl compounds were produced using this strategy, including pyrazoles ( 15 Finally, we explored the application of this convenient strategy to the production of 18 F-difluoromethyl ethers and heteroarenes. As summarized in Scheme 4, using Sanford and Scott's procedure for the preparation of [ 18 F]AgF, [51] used previously by us for 18 F-desulfurative fluorination, [47] we explored the reaction of three DMBDT derivatives. In each case the reactions proceeded smoothly and in high radiochemical conversion (RCC) to provide the desired 18 F-difluoromethyl product.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…[12] In the case of aromatic nucleophilic substitution, leaving groups like F (isotope exchange), Me 3 N + , NO 2 or other halogens have been used. [13] …”
Section: Introductionmentioning
confidence: 99%
“…Appropriate leaving groups such as halogens or sulfonates are required for the introduction into aliphatic groups, combined with almost water‐free conditions, a sufficient solubility in organic solvents and high temperatures, since fluoride is a bad nucleophile [12] . In the case of aromatic nucleophilic substitution, leaving groups like F (isotope exchange), Me 3 N + , NO 2 or other halogens have been used [13] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation